Thickness‐Dependent Asymmetric Potential Landscape and Polarization Relaxation in Ferroelectric HfxZr1−xO2 Thin Films through Interfacial Bound Charges. (26th June 2019) - Zhu, Ying; Ning, Hongkai; Yu, Zhihao; Pan, Qiang; Zhang, Chunchen; Luo, Chen; Tu, Xuecou; You, Yumeng; Wang, Peng; Wu, Xing; Shi, Yi; Wang, Xinran
Abstract: The negative capacitance (NC) effect in ferroelectric materials provides a possible solution to break the Boltzmann tyranny and realize steep‐slope field‐effect transistors (FETs) with sub‐60 mV dec −1 subthreshold slope (SS). HfO2 ‐based ferroelectrics (FE) have attracted great attention as dielectric candidates for NCFETs due to their excellent scalability and compatibility with complementary metal–oxide–semiconductor technology. However, understanding of the ferroelectric properties of HfO2 ‐based FEs, especially at reduced thickness, is still at an early stage. The quasistatic polarization relaxation behavior of ferroelectric Hf x Zr1− x O2 (HZO) thin films below ≈50 nm is reported. Universal asymmetries in coercive voltage and remanent polarization in HZO films deposited on various substrates are observed. The asymmetry is strongly thickness dependent and is related to interface bound charges. These findings suggest that the symmetric double‐well free energy landscape in ideal FEs is not a priori applicable to thin films, which has important implications for HZO‐based devices. It is found, through numerical simulations, that the asymmetric potential landscape can reduce SS in NCFETs without suffering from hysteresis. These results provide new insights toward understanding the mechanisms of FE devices and highlight the need for further efforts to investigate interface‐related phenomena in HZO. Abstract : An interface‐charge‐induced polarization relaxation of Hf x Zr1− x O2 thin film that results in universal thickness‐dependent asymmetries in coercive voltage and remanent polarization is reported. These results suggest that the double‐well potential landscape in ideal ferroelectrics should be modified to account for interface effects in technologically relevant thin films. Such modification will have important consequences for ferroelectric devices.